Spatial behavior of anthracnose in the avocado crop in Coatepec Harinas and Tenancingo, State of Mexico - Tapia-Rodríguez, Atenas; Ramírez-Dávila, José Francisco; Figueroa-Figueroa, Dulce Karen; Gutiérrez-Rodríguez, Francisco; Ruiz-Orta, Alfredo (Ecosistemas y Recursos Agropecuarios, 2023)
Anthracnose is a fungal disease present in the avocado crop that causes considerable economic losses for the productive sector of the State of Mexico.To target control measures,it is important to know the spatial behavior and the dynamics that the disease follows under field conditions.The application of geostatistical methods facilitates this work.For this reason, the objective of this study was to determine the spatial behavior of anthracnose in the Hass avocado crop in Coatepec Harinas and Tenancingo,two producing municipalities in the State of Mexico using classical and geostatistical statistics.The results obtained through classical statistics did not show the real behavior of anthracnose because,in both municipalities,there were adjustments to a Negative Binomial representation as well as to a Poisson distribution.With the use of geostatistics,it was possible to obtain the representation of the spatial behavior of the disease through maps, which show the presence of aggregation centers;the semivariograms for each sampling date presented distributions adjusted mostly to Gaussian and exponential models with ranges that fluctuated between 12 and 56 m,indicating association between the data;likewise,the highest percentage of infected area was 99% for the first sampling in April, while for the first sampling in November,the highest percentage was 98% in both municipalities.Geostatistics makes it possible to know precisely what are the distribution patterns followed by diseases such as anthracnose in avocado-growing areas in the State of Mexico and facilitates the implementation of integrated management programs more effectively, thus contributing to reducing the excessive use of products chemicals, favoring the obtaining of more innocuous fruits.